Balanga Tech Campus Business Incubator and Makerspace for Balanga's university town site - San Juan, Angelica B.
Being the education center of the province of Bataan, the City of Balanga aims to become a University Town this year, 2020. Through the University Town Ordinance, a land area of 42 hectares was declared as the University Town site, found at the heart of urban development within the city. Currently, the city's focus on education is supported and improved through the local government's active programs; however, thereis no clear direction on what sector or speciality is to be developed and focused on. Moreover, there is a mismatch regarding the city's research development concerns and employmend demands. With this, a facility is envisioned to become the center point of the University Town's economical and education success for Balanga City. The Balanga Tech Campus, which is an integration of a business incubatorand makerspace, aims to physically connect the academic institutions, government, and the surrounding community within and beyond the university town site through the provision of spaces and facilities that will cater start-ups and technology-related business, as well as facilities that shall complement with the academic environment.